Household survey panels: How much do following rules affect sample size - Schonlau, M; Watson, N; Kroh, M (My University, 2014)
In household panels, typically all household members are surveyed. Because household composition changes over time, so-called following rules are implemented to decide whether to continue surveying household members who leave the household (e.g. former spouses/partners, grown children) in subsequent waves. Following rules have been largely ignored in the literature leaving panel designers unaware of the breadth of their options and forcing them to make ad hoc decisions. In particular, to what extent various following rules affect sample size over time is unknown. From an operational point of view such knowledge is important because sample size greatly affects costs. Moreover, the decision of whom to follow has irreversible consequences as finding household members who moved out years earlier is very difficult. We find that household survey panels implement a wide variety of following rules but their effect on sample size is relatively limited for a couple of decades. Even after 25 years, the rule “follow only wave 1 respondents” still captures 85% of the respondents of the rule “follow everyone who can be traced back to a wave 1 household through living arrangements” in the SOEP. Once children of permanent sample members start moving out, following such children greatly affects sample size. This effect is noticeable after 25 years in the PSID. Unless attrition is low, there is no danger of an ever expanding panel because even wide following rules do not typically exceed attrition. Grown children of permanent sample members with their own households have a significantly lower attrition rate than first wave respondents in the PSID. Presence of a spouse or a child in a household does not affect attrition; however, presence of other household members significantly increases attrition.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology